2012
DOI: 10.1016/j.physletb.2012.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Holographic superconductor/insulator transition with logarithmic electromagnetic field in Gauss–Bonnet gravity

Abstract: The behaviors of the holographic superconductors/insulator transition are studied by introducing a charged scalar field coupled with a logarithmic electromagnetic field in both the Einstein-Gauss-Bonnet AdS black hole and soliton. For the Einstein-Gauss-Bonnet AdS black hole, we find that: i) the larger coupling parameter of logarithmic electrodynamic field b makes it easier for the scalar hair to be condensated;ii) the ratio of the gap frequency in conductivity ω g to the critical temperature T c depends on b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
41
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 41 publications
1
41
0
Order By: Relevance
“…In order to understand the influences of the 1/N or 1/λ (λ is the 't Hooft coupling) corrections on the holographic dual models, there have been a lot of works studying the holographic superconductors with the higher derivative correction related to the gravity [10][11][12] and the gauge field [13][14][15][16][17][18][19][20][21][22]. Recently, an s-wave holographic dual model with Weyl corrections has been constructed in order to explore the effects beyond the large N limit on the holographic superconductor [23].…”
Section: Introductionmentioning
confidence: 99%
“…In order to understand the influences of the 1/N or 1/λ (λ is the 't Hooft coupling) corrections on the holographic dual models, there have been a lot of works studying the holographic superconductors with the higher derivative correction related to the gravity [10][11][12] and the gauge field [13][14][15][16][17][18][19][20][21][22]. Recently, an s-wave holographic dual model with Weyl corrections has been constructed in order to explore the effects beyond the large N limit on the holographic superconductor [23].…”
Section: Introductionmentioning
confidence: 99%
“…It is worth noting that the gauge field φ depends on the power parameter q of the Power-Maxwell field at the asymptotic AdS region (r → ∞). This is in contrast to the case of holographic superconductor with other nonlinear electrodynamics such as Born-Infeld [29][30][31] and Born-Infeld-like electrodynamics [25,26].…”
Section: Jhep04(2016)058mentioning
confidence: 78%
“…However, it is interesting to investigate the effects of nonlinear electrodynamics on the properties of the holographic superconductor both in Einstein as well as Gauss-Bonnet gravities. Considering three types of nonlinear electrodynamics, namely, Born-Infeld, Logarithmic and Exponential nonlinear electrodynamics, and using numerical methods, it has been observed that, in the Schwarzschild AdS black hole background, the higher nonlinear electrodynamics corrections make the condensation harder [25,26]. The effects of an external magnetic field on the holographic superconductors in the presence of nonlinear corrections to the usual Maxwell action were examined in [27,28].…”
Section: Jhep04(2016)058mentioning
confidence: 99%
“…The studies in Gauss-Bonnet gravity were presented in [26,30], the effects of the Weyl corrections on p-wave holographic phase transitions [27] were studied in [28]. The p-wave holographic superconductors in different gravity backgrounds [29], and in the presence of non-linear electrodynamics [31,32] and other non-trivial conditions [33][34][35] have been elaborated.…”
Section: Jhep03(2016)215mentioning
confidence: 99%